Fitness Levels and Gender Are Related With the Response of Plasma Adipokines and Inflammatory Cytokines in Prepubertal Children - Llorente-Cantarero, Francisco Jesus; Aguilera, Concepción M.; Perez-Navero, Juan Luis; Gil, Angel; Benitez-Sillero, Juan de Dios; Gil-Campos, Mercedes (Frontiers in Nutrition, 2022)
Background and aim: Changes in adipokines have been related with the development of metabolic syndrome, normally associated with obesity, and other risk factors. Fitness seems to promote a healthy cardiovascular status and could influence this development, just from childhood. Therefore, the present study aimed to evaluate the relationship between fitness levels and adipokines and inflammatory blood biomarkers in prepubertal children. Methods: 137 healthy normal-weight prepubertal children were recruited from local schools and divided into two groups according to fitness levels – low cardiovascular fitness group (LF) and equal or higher cardiovascular fitness group (HF)– after performing the fitness tests. Anthropometric parameters, blood pressure (BP) and plasma leptin, resistin, adiponectin, tumor necrosis factor-alpha, hepatic growth factor, interleukin (IL)-8, monocyte chemoattractant protein-1, nerve growth factor (NGF), and plasminogen activator inhibitor-1 (PAI-1) were measured. Univariate analysis of variance, comparative analysis, binary logistic regression, stepwise linear regression and principal component analysis (PCA) were conducted to evaluate the association between fitness, BMI, gender the biomarkers. Results: Girls and boys with HF presented lower WC Z-score, BMI Z-score, systolic BP (only boys) as well as lower levels of leptin and NGF compared with their respective LF group. Regarding the association between variables, fitness presents an inverse relationship with BMI Z-score, leptin, PAI-1, HOMA-IR, resistin, IL-8 and NGF. Conclusion: Higher fitness levels might have a protective effect against of development of obesity and metabolic risk factors, just from the prepubertal stage